Philosophical Mediation in Cultural Diplomacy - Mažeikis, Gintautas (Eidos. A Journal for Philosophy of Culture, 2024)
This paper explores two primary propositions: a) philosophical mediation is a vital component of cultural diplomacy, historically evolving from a practice based on cultural sensitivity, critical analysis, and public discourse; b) in the realm of diplomacy, philosophical mediation delineates the principles of cultural “adaptability,” addressing local social dynamics and epistemologies where the art of negotiation is applied. This approach does not seek to dismantle or expose prejudices, ideological and religious beliefs, pseudo-historical anticipations, and political narratives. Instead, philosophical mediation strives for a delicate equilibrium; supporting tolerance of accepted traditions alongside democratic and constructive criticism, and promoting enlightenment and progress.